Revision of Tricholepis DC. (Asteraceae) in India - Chaudhary, L. B.; Pandey, A. K. (Rheedea, 2001)
The genus Tricholepis with 10 species and one variety in India is revised. Out of these, four taxa viz., T. amplexicaulis, T. glaberrima var. glaberrima, T. glaberrima var. angustifolia and T. radicans are endemic to India. A key to the section of the genus and species, taxonomic descriptions and illustrations are provided along with data on phenology, distribution, ecology and uses. Four species namely, T. chaetolepis, T. montana, T. nakaoi and T. stewartei are excluded in the present work.